2003
DOI: 10.1172/jci15937
|View full text |Cite
|
Sign up to set email alerts
|

Novel transglutaminase inhibitors reverse the inflammation of allergic conjunctivitis

Abstract: 2 ), including uteroglobin and lipocortin-1 (annexin I). Uteroglobin and lipocortin-1 retain several conserved sequences. Based on these sequences, several nonapeptides (antiflammins) were synthesized. These nonapeptides were shown to have anti-inflammatory effects in vitro and in vivo, possibly by inhibiting PLA 2 . Subsequent research showed that PLA 2 is activated by transglutaminase 2 (TGase 2). We hypothesize here that TGase 2 inhibitors may increase the anti-inflammatory efficacy of inhibiting PLA 2 acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 40 publications
3
81
0
Order By: Relevance
“…In this study, we provide evidence that TG2 could be an important factor in the mechanism through which sepsis develops, acting at multiple levels. Previous studies have shown that TG2 inhibitors can be useful in reversing some inflammatory processes (37). In the present study, we demonstrated that the ablation of TG2 confers resistance to LPS-induced septic shock in mice.…”
Section: Discussionsupporting
confidence: 70%
“…In this study, we provide evidence that TG2 could be an important factor in the mechanism through which sepsis develops, acting at multiple levels. Previous studies have shown that TG2 inhibitors can be useful in reversing some inflammatory processes (37). In the present study, we demonstrated that the ablation of TG2 confers resistance to LPS-induced septic shock in mice.…”
Section: Discussionsupporting
confidence: 70%
“…Mehta et al suggested that increased TGase 2 expression in MCF-7/DOX cells augmented the binding of integrins to extracellular matrix proteins (31). Increased expression of TGase 2 correlates with increased cell motility and adhesion (20,32,33), and cell adhesion induces activation of focal Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Both modifications significantly augmented the activity of sPLA 2 . Peptide inhibitors of TG2 or peptides with dual inhibition of TG2 and PLA 2 significantly inhibited the inflammation associated with allergic conjunctivitis induced by ragweed in a guinea pig model (78) and lung inflammation induced by lipopolysaccharide (79). Both factor XIII and tissue TG have roles in regulating macrophage adhesion, migration and phagocytosis (50,74,80).…”
Section: Role Of Transglutaminases In Inflammationmentioning
confidence: 99%